Development of a Didactic Demonstrator for Aeroacoustic Evaluations of Ducts - Schode, Stefan; Boysen, Jan; Mayrhofer, Dominik; Kraxberger, Florian; Heidegger, Patrick; Wurzinger, Andreas; Czwielong, Felix; Maurerlehner, Paul (30th AIAA/CEAS Aeroacoustics Conference, 2024, 2024)
Higher education by means of aeroacoustic laboratories is crucial for the future development of ever quieter and more efficient transportation technologies. The practical training contributes to improving safety, understanding the physical relationships between aerodynamic performance and aeroacoustic noise emission, and provides interdisciplinary training for the next generation of professionals in the field. Hence, this ongoing project adapts an existing aero- and vibroacoustic test rig for low-Mach-number flows in a pipe. It targets the development of a high-quality demonstrator for teaching flow-induced sound generation in ducts. The initial test rig was designed to study flow-induced sound in pipe structures for automotive applications, where low cabin noise is becoming an increasingly important purchase criterion. The test rig comprises a high-pressure/low-Mach-number centrifugal blower, adaptable pipe sections, acoustic absorbers to decouple the test section from blower noise, and an anechoic termination to mitigate acoustic reflections at the pipe exits. Multiple sensors are inserted to track the system operation, flow conditions, internal sound radiation and transmission, and surface vibrations. The highprecision test rig is being transformed into a more transportable and easily accessible teaching tool with the aim of providing optimal conditions for didactic applications.
CRIS-Team Scopus Importer:2024-09-13